The Realities of Primary Care : Variation in Quality of Care Across Nine Countries in Sub-Saharan Africa - Andrews, Kathryn (World Bank, Washington, DC, 2021)
The COVID-19 pandemic has highlighted the centrality of primary care in protecting people’s health and well-being during and beyond crises. It has also provided an opportunity to strengthen and redesign primary care so that it will better serve its purpose. However, to-date there is limited evidence on the quality of service delivery in primary care. Service Delivery Indicators surveys have attempted to fill this gap. Using Service Delivery Indicators surveys of 7,810 health facilities and 66,151 health care providers in nine Sub-Saharan African countries, this paper investigates the quality of care across five domains to understand a citizen’s experience of primary care in his/her country. The results indicate substantial heterogeneity in the quality of primary care service delivery between and within countries. The availability of basic equipment, infrastructure, and essential medicines varies—public facilities, facilities in rural areas, and non-hospitals are more lacking compared with private facilities, urban facilities, and hospitals. In terms of patient care, health care providers’ ability to correctly diagnose and treat common health conditions is low and variably distributed. COVID-19 has catalyzed a long overdue health system redesign effort, and the Service Delivery Indicators surveys offer an opportunity to examine carefully the quality of service delivery, with an eye toward health system reform.